Fiscal Adjustments and Social Spending : An Analysis of the Indian Economy - Khoja, Ishfaq Ahmad; Khan, N. A. (Arthshastra Indian Journal of Economics & Research, 2019)
The higher and unsustainable levels of debt have forced the economies to undergo consolidation policies to improve their fiscal position. However, such policies can impact both economic growth and welfare spending owing to their deficit dependence. The current study analyzed the debt dependence of welfare spending and tried to evaluate the impact of consolidation strategies on the long - term social and welfare spending in case of the Indian economy. The study employed the time - series data covering the time period from 1990 - 2018 concerning 13 variables broadly grouped under three headings, that is, spending on education, health, and welfare. The study utilized the technique of generalized method of moments technique (GMM). The study found that the deficit financing nature of the government is a significant determinant of social and welfare spending in the Indian economy. A 1% increase in the growth rate of deficit financing was found to augment the growth rate of spending on education by 0.13%, on health by 0.03%, on welfare by 0.15% with an overall impact of 0.11%. Such a debt dependence by the social and welfare spending raised doubts that a consolidation design may further endanger the already stagnating social and welfare spending. This is mainly if a consolidation programme pursued with an aim to infuse fiscal prudence heavily concentrates on the quantity rather than the quality of the design.